2006
DOI: 10.1007/s00425-006-0319-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity induces reorientation of cortical microtubules and modifies growth anisotropy in azuki bean epicotyls

Abstract: We examined the changes in the orientation of cortical microtubules during the hypergravity-induced modification of growth anisotropy (inhibition of elongation growth and promotion of lateral growth) in azuki bean (Vigna angularis Ohwi et Ohashi) epicotyls. The percentage of cells with transverse microtubules was decreased, while that with longitudinal microtubules was increased, in proportion to the logarithm of the magnitude of gravity. The percentage of cells with longitudinal microtubules showed an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 27 publications
5
61
0
1
Order By: Relevance
“…19,20 In our recent study, we found that gadolinium ions decreased the alignment angle of epidermal cell files and that of cortical region of azuki bean epicotyls, cells with transverse cortical microtubules were predominant at 1 g. Hypergravity induces reorientation of cortical microtubules from transverse to longitudinal directions. 9 In addition, hypergravity increased transiently the expression of γ-tubulin and katanin genes, 10,11 which are assumed to be responsible for reorientation of cortical microtubules. 12 These results suggest that cortical microtubules are involved in gravity resistance.…”
Section: Involvement Of Mechanoreceptors In Gravity Resistancementioning
confidence: 99%
“…19,20 In our recent study, we found that gadolinium ions decreased the alignment angle of epidermal cell files and that of cortical region of azuki bean epicotyls, cells with transverse cortical microtubules were predominant at 1 g. Hypergravity induces reorientation of cortical microtubules from transverse to longitudinal directions. 9 In addition, hypergravity increased transiently the expression of γ-tubulin and katanin genes, 10,11 which are assumed to be responsible for reorientation of cortical microtubules. 12 These results suggest that cortical microtubules are involved in gravity resistance.…”
Section: Involvement Of Mechanoreceptors In Gravity Resistancementioning
confidence: 99%
“…For example, hypergravity promoted reorientation of microtubules into parallel arrays in protoplasts from Nicotiana tabacum (Wymer et al, 1996) and Brassica napus (Skagen and Iversen, 1999). Also, hypergravity induced reorientation of cortical microtubules from transverse to longitudinal directions in azuki bean epicotyls (Soga et al, 2006). Taken together, reorientation of cortical microtubules may be involved in the development by gravity of a short and thick body.…”
Section: Introductionmentioning
confidence: 96%
“…1), we examined the changes in the expression of katanin (VaKTN1) gene in azuki bean epicotyls grown under hypergravity conditions produced by centrifugation. We also examined the effects of lanthanum or gadolinium ions, potential blockers of mechanosensitive calcium ion-permeable channels (mechanoreceptors), on hypergravity-induced changes in expression of VaKTN1, because hypergravity-induced reorientation of cortical microtubules as well as upregulation of expression of VaTUG and VaGCP3 were nullified in the presence of lanthanum and gadolinium ions (Soga et al, 2006(Soga et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In the epidermis of azuki bean epicotyls grown at 1 G, cells with transverse cortical microtubules were predominant. With increasing the gravitational force, the percentage of cells with transverse microtubules was decreased, whereas that with longitudinal microtubules was increased (Soga et al, 2006). In addition, hypergravity increased transiently the expression of γ-tubulin and katanin genes − 72 − Growth of tua6 mutant in space (Soga et al, 2008(Soga et al, , 2009, which are assumed to be responsible for reorientation of cortical microtubules (Murata et al, 2005).…”
Section: Introductionmentioning
confidence: 99%